Vulnerability to the infection STD/Aids in female prisoners of São Paulo-sp, Brazil, assessed by serological technique - Strazza, Leila; Carvalho, Heráclito; Azevedo, Raymundo S; Massad, Eduardo (Brazilian Journal of Sexually Transmitted Diseases, 2003)
Introduction: There is not so revealable in the society than his discases history meanly the “social diseases”, as alcoholism, tuberculosis and syphilis among others. Add aids to this group on the earlier 80’s. We also observed the incarcerated population run high -risk DST/aids infections due their high vulnerability. The arrest condition could be unique to self-care concern. Objective: estimate this population vulnerability identifying their risk behaviour and DST/aids knowledge Methods: To access HIV and anli-pallidum serology and interview 290 female prisoners aboul their age, formal education, race, sexual behaviour, habits and DST/aids knowledge. It was carried out safe-sex workshops based on Paulo Freire’s methods, also named “oppressed pedagogy” that it gives a preference to the movements againsl social exclusion. Results: Prevalence were related to risk behaviour trough contingency tables to obtain OR and chi-square and Fisher tests were performed in order to estimate the statisties significance. The HIV and syphilis prevalence were 13.9% and 22.8% respectively. Conclusion: The high prevalence and the sexual behaviour risk infection associated found in this spccific population suggest the sexual route as huge importance. Preventions DST/aids program and other specially aimed to prisoners neces- sity, to women living recluse in the Penal System, are highly recommended. Syphilis history has to be reminding as an alert to the society behaviour in order to avoid mistakes that has been done in the past.